Multi-Target Antibacterial Mechanism of Moringin From Moringa oleifera Seeds Against Listeria monocytogenes - Wen, Yanlong; Li, Wenyun; Su, Rongzhen; Yang, Min; Zhang, Nan; Li, Ximing; Li, Lingfei; Sheng, Jun; Tian, Yang (Frontiers in Microbiology, 2022)
Moringin [4-(α-L-rhamnosyloxy) benzyl isothiocyanate] is an isothiocyanate extracted from Moringa oleifera seeds. It is the bioactivate form of glucomoringin with various health benefits. However, few studies have examined the antibacterial activity of moringin. This study aimed to investigate the antimicrobial activity and mechanism of moringin against L. monocytogenes. The minimum inhibitory concentration (MIC), and growth curves were used to evaluate the bacteriostatic effect of moringin against L. monocytogenes. Transcriptome analysis by RNA sequencing was performed to elucidate the underlying mechanism of moringin against L. monocytogenes. The transcriptome results were validated. The results showed that moringin inhibited the growth of L. monocytogenes with a MIC of 400 μM. RNA sequencing results showed that the differences in the expression of genes related to the cell wall and membrane biosynthesis, phosphotransferase system (PTS), oxidative stress, energy metabolism, and DNA binding were significantly affected. As with the transcriptome results, the results of the mechanism verification found that moringin damaged the integrity of the cell wall and cell membrane, stimulated oxidative stress, interfered with energy metabolism and DNA replication, and finally led to the death of L. monocytogenes. The present study provides evidence that moringin exhibits strong antimicrobial activity against L. monocytogenes and insight into its potential mechanism.